PENGARUH PEMAHAMAN PERATURAN PERPAJAKAN, KESADARAN WAJIB PAJAK DAN AKUNTABILITAS PELAYANAN PUBLIK TERHADAP KEPATUHAN WAJIB PAJAK - Mahaputri, Ni Nyoman Trysedewi; Noviari, Naniek (E-Jurnal Akuntansi; Vol 17 No 3 (2016), 2016)
Arrears vehicle tax data of SAMSAT Denpasar in 2011-2014 indicated that there are taxpayers who do not comply the tax liabilities. The purpose of this study is to obtain empirical evidence of influence of the tax regulation comprehension, taxpayer awareness, and the accountability of public service on vehicle taxpayer obedience. This study conducted on Samsat Denpasar office. This study population is all registered vehicle taxpayer on SAMSAT Denpasar. Samples of this study are 100 respondents, with accidental sampling method. Data Collection using questionnaire. Data analysis technique is multiple linear regression analysis. Based on the analysis, the tax regulation comprehension, taxpayer awareness, and the accountability of public service have positive influence to the vehicle taxpayer obedience. Coefficient determibation result, as big as 20,4 percent effect and the other 79,6 percent influences by outside research model factors.
Keywords: Vehicle taxpayer obedience, tax regulation comprehension, taxpayer awareness, accountability of public service